2002
DOI: 10.1016/s0092-8674(02)00675-x
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism and Regulation of Chromosomal V(D)J Recombination

Abstract: V(D)J recombination is of fundamental importance to the generation of diverse antigen receptor repertoires. We review our current understanding of the V(D)J recombination reaction and how it is regulated during lymphocyte development. We also discuss how defects in the mechanism or regulation of V(D)J recombination can lead to human disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
755
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 812 publications
(775 citation statements)
references
References 107 publications
5
755
0
5
Order By: Relevance
“…In an attempt to characterize the molecular events that direct the accessibility, a very important study has shown that the RAG complex can access chromosomal RSS only in lymphoid cells and only in the lineage-specific loci (e.g: the Ig loci only in the pro-B cells; the TCR loci only in the pro-T cells) [6]. As this seemed to point to specific chromatin properties, subsequent studies have focused on the role of the nucleosomal structure [7,8]. All the in vitro results obtained so far seem to confirm that a nucleosomal RSS is refractory to binding and cleavage by the RAG proteins [9][10][11]; the studies, however, diverge with regards to the possibility to overcome the block by acetylating the tails of the histones.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to characterize the molecular events that direct the accessibility, a very important study has shown that the RAG complex can access chromosomal RSS only in lymphoid cells and only in the lineage-specific loci (e.g: the Ig loci only in the pro-B cells; the TCR loci only in the pro-T cells) [6]. As this seemed to point to specific chromatin properties, subsequent studies have focused on the role of the nucleosomal structure [7,8]. All the in vitro results obtained so far seem to confirm that a nucleosomal RSS is refractory to binding and cleavage by the RAG proteins [9][10][11]; the studies, however, diverge with regards to the possibility to overcome the block by acetylating the tails of the histones.…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish this BAC from the endogenous Ig locus, a cMyc tag (39 bp) was introduced into the C 1 constant region so that it inserted into, and destroyed, the Xho I site; this generated the BAC, C 1 -T ( Figure 1B). …”
Section: Generation Of a Bac Spanning The 3' Half Of The Ig Locusmentioning
confidence: 99%
“…The generation of an accessible chromatin structure at the RSSs is central to this regulation (reviewed by [1]) and knock-out studies have shown that tissuespecific enhancers play an essential role in regulating this accessibility by restricting it to the correct cell and the correct stage of lymphocyte development [2]. Recombination enhancers have been identified for most immunoglobulin and T cell receptor loci and are often identical to the enhancers that upregulate transcription of the rearranged gene [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations